(untitled) (Nucleus, 2010)
The aim of this work is to discuss some selected application of square wave voltammetry published in the last years. The application focused here cover several electroanalytical fields as the determination of pesticides, metals and others environmental pollutants. These new methodology are simple, fast and sensitivity when compared with the traditional ones such as chromatography and spectrophotometry.